Seasonal Variations in Water Quality of the Ganges and Brahmaputra River, Bangladesh - Tareq, Shafi M; Rahaman, MS; Rikta, SY; Islam, SM Nazrul; Sultana, Mahfuza S (Jahangirnagar University Environmental Bulletin, 2013)
Jahangirnagar University Environmental Bulletin, Vol.2, 71-82, 2013 DOI: http://dx.doi.org/10.3329/jueb.v2i0.16332